Mass point versus whole-body modeling of skiers for performance evaluation in alpine skiing - Hladnik, J.; Svenšek, D.; Jerman, B.; Supej, M. (Scandinavian Journal of Medicine & Science in Sports, 2023)
The altitude differential of the specific mechanical energy, diff(e_mech), is used to evaluate skiing performance. It is defined as the negative differential between the skier's total specific mechanical energy (e_mech) ) and the altitude of the skier's center of mass (COM). Till now, e_merch was obtained upon a mass-point (MP) model of the skier's COM, which neither considered the segmental energies of their relative movements to the COM, nor their rotational kinetic energies. The aims of the study were therefore: (a) to examine the deviations diff (e_mech) in between the MP and a more complex linked segment (LS) skier model consisting of 15 rigid bodies, which encountered the aforementioned defectiveness, (b) to compare the energy fluctuations of the two skier models, and (c) to investigate the influence of the gate setup on (a) and (b) in giant slalom. Three-dimensional whole-body kinematics of nine skiers was measured using a global navigation satellite system and an inertial motion capture system while skiing on a predefined course divided into a turny and open gate setup. Mechanical energies including their altitude differentials were calculated for the LS and MP models. There were no significant differences in e_merch and diff (e_merch) ski turn averages, as in individual data points, between both skier models for both analyzed gate setups. The energies additionally considered by the LS model presented a negligible part regardless of the gate setup. In conclusion, the MP skier model is sufficiently accurate for the evaluation of the skiing performance with.